Implementation of Good Corporate Governance Principles at PT. Pelindo Daya Sejahtera - Muhammad Hafidz,; Megawati, Suci; Rahaju, Tjitjik; Tauran, Tauran; Pascua, Jyla Grace M. (Journal of Social Dynamics and Governance, 2026)
This study aims to analyze the implementation of the principles of Good Corporate Governance (GCG) at PT Pelindo Daya Sejahtera. The implementation of GCG is an essential aspect of realizing corporate governance that is transparent, accountable, responsible, independent, and fair, while also reflecting the company's commitment to supporting good governance practices in State-Owned Enterprises (SOEs) in accordance with the Regulation of the Minister of State-Owned Enterprises of the Republic of Indonesia Number PER-2/MBU/03/2023. This study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The analysis was based on George C. Edward III's policy implementation model, which consists of four indicators: communication, resources, disposition, and bureaucratic structure. The research result indicate that the implementation of Good Corporate Governance principles at PT Pelindo Daya Sejahtera has been carried out relatively well, particularly in the aspects of disposition and bureaucratic structure, as evidenced by the existence of clear Standard Operating Procedures (SOPs), an established organizational structure, and strong management commitment to promoting good corporate governance. In terms of communication, information has been disseminated through socialization programs and the use of simplified language to ensure that it is easily understood by all employees. However, challenges remain in the resource aspect, particularly due to the large number of employees, which has resulted in uneven dissemination of GCG socialization. Therefore, improvements in human resource management are necessary to enhance the equitable understanding of GCG principles among employees.